Features of the HRV, endocrine and metabolic parameters in persons whose immune status is susceptible or resistant to chronic stress - Oleksandr Lukyanchenko; Oksana Mel'nyk; Olena Gozhenko; Walery Zukow; Igor Popovych (Kazimierz Wielki University, 2020)
Background. In the previous studies, we compared the individuals who were almost identical to the average value of LF/HF ratio and its dispersion, but with opposite deviations from the norm of immunity. Two profiles of EEG have been created that reflect the differences between the two clusters. The first profile contains the parameters that in stress-sensitive individuals are in the zone of narrowed norm, whereas in stress-resistant individuals they are to some degree elevated, or at least exceed those in stress-sensitive individuals. The second profile contains EEG parameters, each of which in stress-resistant individuals is lower than that of stress-sensitive individuals. The purpose of this study is to clarify the features of the HRV, endocrine and metabolic parameters in persons whose immune status is susceptible or resistant to chronic stress. Materials and Methods. The object of observation were 32 men and 8 women with chronic pyelonephritis in remission. The criterion for inclusion was the magnitude of the sympathico-vagal balance index LF/HF which exceeded the age norm by 0,5 σ. We determined spectral parameters of HRV, plasma levels of principal adaptation Hormones, plasma and daily urine levels of the Electrolytes and Nitrous metabolites as well as plasma Lipoproteines spectrum. Results. Discriminant analysis revealed that Testosterone is the main factor that conditioning the sensitivity of immune status to sympathotonic shift in autonomic regulation in chronic stress. Sensitizing (immunosuppressive) factors are also Ca/K-ratio of plasma and total Cholesterol, instead LD LP Cholesterol, Creatininuria, P/Ca-ratio of urine, spectral power of VLF band HRV as well as entropy of HRV are desensitizing (immunoprotective) factors. Conclusion. The susceptibility or resistance of the immune status to the stress sympathotonic shift of autonomic regulation is conditioned by the combination of EEG, HRV, endocrine and metabolic parameters.